The bus ride that changed history : the story of Rosa Parks - Edwards, Pamela Duncan; Shanahan, Danny (Boston : Houghton Mifflin, 2005)
A cumulative narrative recounting the story of Rosa Parks, an African-American woman who sparked the civil rights movement when she refused to give up her seat on a bus in Montgomery, Alabama, for a white man.
Booklist
Horn Book
School Library Journal
2.2
K-3
K-3
Keywords: Parks, Rosa, -- 1913-2005 -- Juvenile literature; Parks, Rosa, -- 1913-2005.; Parks, Rosa, -- 1913-2005.; African Americans -- Civil rights -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; African Americans -- Alabama -- Montgomery -- Biography -- Juvenile literature; Civil rights workers -- Alabama -- Montgomery -- Biography -- Juvenile literature; Segregation in transportation -- Alabama -- Montgomery -- History -- 20th century -- Juvenile literature; African Americans -- Biography; Civil rights workers; Segregation in transportation; Women -- Biography; African Americans -- Biography; Civil rights workers -- Biography; Segregation in transportation; Women -- Biography; Montgomery (Ala.) -- Race relations -- Juvenile literature